Controlled surface functionalization of multiwall carbon nanotubes by HNO3 hydrothermal oxidation - V. Likodimos; Steriotis, T.A.; Papageorgiou, S.K.; Romanos, G.E.; Marques, R.R.N.; Rocha, R.P.; Faria, J.L.; Pereira, M.F.R.; Figueiredo, J.L.; Silva, A.M.T.; P. Falaras (Carbon, 2014)
Controlled surface functionalization is demonstrated by nitric acid hydrothermal oxidation on multiwall carbon nanotubes (MWCNTs). The formation and evolution of oxygen functional groups were systematically investigated as a function of the HNO3 concentration on MWCNTs with different structural and morphological characteristics, employing temperature-programmed desorption coupled with mass spectrometry, thermogravimetry and differential scanning calorimetry, Raman spectroscopy and N2 porosimetry analysis. Hydrothermal treatment provides controlled MWCNT modification by specific oxygen functionalities at amounts determined by the morphology, texture and crystallinity of the pristine materials. Hydrothermal oxidation competes well with the harsh boiling nitric acid treatment regarding the total amount of oxygen functionalities, while requiring much lower amounts of oxidizing agent and, most importantly, reducing amorphous carbon deposits on the MWCNT surface, a major drawback of aggressive liquid phase oxidation methods. Detailed pore structure analysis revealed a progressive increase of the surface area upon hydrothermal functionalization, whereas the mesopore structure varied consistently with the intrinsic MWCNT properties related to the packing of the nanotube bundles and the reduction of amorphous carbon. These advantageous features render nitric acid hydrothermal oxidation an efficient functionalization process to fine tune and optimize the surface chemistry of MWCNTs for target applications, circumventing the need for additional purification post-processing. © 2013 Elsevier Ltd. All rights reserved.